Provenance Differences in Water-Use Efficiency Among Sessile Oak Populations Grown in a Mesic Common Garden - Rabarijaona, Arivoara; Ponton, Stéphane; Bert, Didier; Ducousso, Alexis; Richard, Béatrice; Levillain, Joseph; Brendel, Oliver (Frontiers in Forests and Global Change, 2022)
Context As a widespread species, sessile oak (Quercus petraea) populations occupy a wide range of ecological conditions, with large gradients of soil water availability. Drought acclimation involves a plastic increase in water-use efficiency (WUE), a trait that is easily measured using the carbon isotope composition (δ13C). However, the question remains whether WUE is an adaptive trait that impacts the fitness of trees in natural environments. Objectives and Methods To investigate whether WUE was a drought-adaptive trait, we studied a sample of 600 trees originating from 16 provenances, grown for 21 years in a common garden. Intrinsic WUE (WUEi), estimated from tree ring δ13C, was compared among and within populations for three climatically contrasted years. The adaptive character of WUEi was evaluated by relating population mean WUEi, as well as its plasticity to drought, to the pedoclimatic conditions of their provenance sites. The contribution of WUEi to tree and population fitness was finally assessed from the relationship between WUEi and tree radial growth (GI). Results Significant differences in WUEi were found among populations but a much larger variability was observed within than among populations. The population WUEi of the juvenile oak trees growing in the relatively mesic conditions of the common garden showed no relationship with a modeled water deficit index for the provenance sites. However, a higher population WUEi plasticity to severe drought was related to a higher proportion of silt and carbon and a lower proportion of sand in the soil of the provenance sites. In response to severe drought, populations with a higher increase in WUEi showed a lower decrease in GI. Populations with lower GI reduction were from sites with higher vapor pressure deficit in May–July (VPD). For the wet year only, populations with a higher WUEi also had a higher GI. Conclusion The correlations observed at the common garden site between (i) population means of WUEi plasticity to drought and soil texture of the provenance sites, and (ii) GI plasticity to drought and VPD, suggested a local adaptation of sessile oak.